Assessment of structurally-constrained spanloads for span-extended wing design - Bragado Aldana, Estela; Riaz, Atif (American Institute of Aeronautics and Astronautics (AIAA), 2024)
High aspect ratio wings are receiving increased attention as a promising solution in pursuit of reducing aviation's environmental impact. To address the challenging trade-off between induced drag and weight, this paper presents an overview of the evaluation of the synthesis of wing aerodynamic and structural requirements for the design of high aspect ratio wings. This is done as a means to improve overall vehicle performance and enlighten the relevant complexities of the design process. A physics-based framework for the conceptual design stage has been composed to produce a set-based design space for the analysis of aircraft with high aspect ratio wings under prescribed aero-structural requirements, integrating state-of-the-art computational models and in-house developed methodologies to create a multi-disciplinary and multi-fidelity design environment. This enables to conduct comparative performance analyses of the proposed concepts relative to a conventional airliner. The impact of such a design approach is assessed at a mission performance level, yielding up to a 30% reduction in structural weight growth with span extension and increasing range-to-weight capabilities by 5%.
Keywords: Lift to Drag Ratio; Aerodynamic Properties; Structural Displacement; High Aspect Ratio; Civil Aircraft; Aviation; Computational Modeling; Aircraft Configurations; Aerodynamic Efficiency; Top Level Aircraft Requirements